Precursor molarity effect on the memristive behaviour of spin coated titania thin film: article / Mohd Adib Mahmudin - Mahmudin, Mohd Adib (2014)
This paper presents the memristive behaviour of the titania thin film. The precursor molarity of titania thin film was varied to 0.05M, 0.1M, 0.2M, 0.3M, and 0.4M to study the effect of precursor molarity on the memristive behaviour of titania thin film. From the observation, despite of the precursor molarity differences, the resistance ratios of the best switching loop for all the samples shows no significant changes. However, it was found that the sample with less precursor molarity required lesser time to produce the stable switching loop compared to the sample with higher precursor molarity.